(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The aim of the current research is to identify the level of primary school pupils’ possession of numerical skills. In order to achieve the goal of the research, a test was prepared consisting of (23) objective items and distributed over five skills, namely (numbers and numbers, arithmetic operations and estimation of their outputs, finding numerical relationships, numerical problems, and mental and written arithmetic), and the apparent validity of the test was calculated by presenting it to a group of The arbitrators and experts and the validity of the internal consistency in the light of the following indicators (the relationship of the item score with the total score of the test, the relationship of the item with the skill attached to it). As for the reliability of the test, it was calculated using the Keuder-Richardson equation (K - R20), and it was applied in the academic year 2021-2022 on a sample of The sixth grade students in the General Directorate of Education of Maysan Governorate, consisting of (240) students, applied the test for a period of three days, starting from Sunday corresponding to (3/13/2022), and the following statistical methods were used (difficulty coefficient, discrimination coefficient, effectiveness of wrong alternatives , chi-square, T-test for one sample and for two samples) using the SPSS statistical package, and the following results were reached: There is a weakness in the level of primary school pupils’ possession of numerical skills.The two researchers recommended several recommendations, including educating mathematics teachers of the importance of numerical skills among female students as one of the important goals of teaching mathematics, as well as qualifying and training them through training courses. Some proposals were also put forward, including: conducting a study on the causes of difficulties in learning numerical skills and the extent of their spread in Baghdad or in other provinces.Keywords: numerical skillsPrimary